KINERJA UNIT PELAYANAN PUBLIK MENURUT PERMENPAN NOMOR 25 TAHUN 2006 (Studi Kasus pada Kantor SAMSAT Kota Samarinda) - Zakiyah, Siti (Jurnal Borneo Administrator, 2007)
Various Complaints from society that often occur nowadays againts the service given by government indicate the unprofessional bureucracy performance in giving service to society. Performance of public service in Indonesia still remain unprofessional as the consequences of Indonesia’s bureaucracy that is not designed to “serve the society/abdi masyarakat”. Effort to improve the public service have been done by State Minister for Apparatus Empowerment (Menpan) trough some policies related to the public service such as the latest Menpan Regulation No. 25/ /M.PAN/04/2006 concerning Assesment of Performance of Public Service Unit that offer Excellent Service Award for Service Unit with the best performance. This article tries to identify the implementation of Performance Indicators of SAMSAT Office in Samarinda based on that Regulation.  Keywords: birokrasi ,kinerja unit pelayanan, pelayanan prima